Criminal Law Politics and Punishment Theories: A Comparative Study of Retributive vs. Restorative Justice in Indonesia and Georgia - Nur Ainy Amira Puspitaning Suwandi; Lutfi Nur Aida; I Gede Widhiana Suarda; Y A Triana Ohoiwutun; Maia Kapanadze (PATTIMURA Legal Journal, 2025)
Introduction: The debate between retributive and restorative justice remains a central issue in the politics of criminal law across jurisdictions. Indonesia and Georgia represent two countries undergoing legal transitions with distinct historical and socio-political contexts, yet both face similar challenges in determining the orientation of their penal policies. Purposes of the Research: This study aims to analyze the differences in the application of retributive and restorative penal theories within the criminal law policies of Indonesia and Georgia, as well as to identify the factors influencing these orientations. Methods of the Research: The research adopts a normative legal method with a comparative approach, examining statutory provisions, legal doctrines, and relevant judicial decisions. Results Main Findings of the Research: The findings reveal that Indonesia continues to rely on its colonial legacy through the Criminal Code, which predominantly reflects a retributive paradigm, while gradually incorporating restorative principles in specific legislation such as the Juvenile Criminal Justice System Law. Conversely, Georgia, which previously enforced an extreme zero tolerance policy rooted in a retributive approach, has shifted toward restorative justice within its juvenile justice system through the enactment of the Juvenile Justice Code of 2015. The novelty of this research lies in its comparative analysis, which uncovers how historical, cultural, political, socio-economic, and legal factors shape each country’s penal orientation. These findings contribute to the development of comparative criminal law scholarship and provide valuable insights for promoting more balanced penal policies that integrate both retributive and restorative justice.